University Students' Perceptions on Using Quizlet Digital Flashcards to Learn English Vocabulary - Rusydina Khumaida; Christianti Tri Hapsari (Journal of Social Research, 2026)
English vocabulary is a fundamental component of language proficiency, yet many university students find conventional memorization methods ineffective and demotivating. The rise of digital learning tools, such as Quizlet, has introduced new possibilities for engaging vocabulary instruction; however, research specifically examining university students' perceptions of Quizlet in the EFL context remains limited. This study aims to investigate how university students perceive the use of Quizlet digital flashcards to learn English vocabulary and to identify the vocabulary learning strategies they employ through the application. A qualitative research design was adopted, with data collected from 20 English Education university students (Semester 8) at a university in Semarang through a 20-item closed-ended Likert-scale questionnaire and semi-structured interviews with three purposively selected participants. Data were analyzed using the Miles and Huberman qualitative data analysis model and interpreted through Davis's (1989) Technology Acceptance Model (TAM) and Schmitt's (1997) Vocabulary Learning Strategies (VLS) framework. The findings reveal that students hold highly positive perceptions of Quizlet's system design, ease of use, usefulness, and attitude toward use; however, a significant attitude-behavior gap was identified, as many students do not use Quizlet regularly despite their favorable perceptions. Regarding vocabulary learning strategies, students actively employ determination, social, and memory strategies, with flashcard-based long-term retention receiving the strongest endorsement. Cognitive strategies involving multi-modal practice were also evident, while metacognitive strategy use revealed high self-evaluation but low proactive study planning. These findings suggest that Quizlet is a promising supplementary EFL vocabulary learning tool, most effective when integrated into structured, instructor-guided pedagogical activities.